The Effect of Job Stress and Motivation on Employee Performance of Jabodetabek Domicile with Work Method Policy as an Intervening Variable - Agustina, Kartika; Safaria, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research purpose is to find relationship among work stress on work method policies, work motivation on work method policies, work stress to employee performance, work motivation to employee performance, work method policies to employee performance, work stress to employee performance through work method policies as intervening variables, work motivation to employee performance through work method policies as intervening variables. Respondents in this study were workers in the JABODETABEK area totaling 161 people. The results obtained are work stress has a significant effect to work method policy, motivation has a significant effect to work method policy, work stress has a significant effect to performance, motivation has a significant effect to performance, work method policy has a significant effect to performance, work stress has a significant effect on performance through work method policy as intervening variable, motivation has a significant effect to performance through work method policy as intervening variable